Implementation of Academic Supervision by the Head of Madrasah Aliyah Negeri Tolitoli in Tolitoli, Central Sulawesi - Nursida; Ahmad Sunaedi; Hamdi Rudji (Journal of Educational Management and Islamic Leadership (JEMIL), 2022)
This research is motivated by the success that the Head of Madrasah Aliyah Tolitoli has in carrying out academic supervision of the head of the madrasa, especially on the performance of teachers at MAN Tolitoli, in this regard researchers are interested in conducting research on the Implementation of Academic Supervision by the Head of Madrasah Aliyah Negeri Tolitoli. The research was carried out at MAN Tolitoli by distributing questionnaires to all teachers at MAN Tolitoli as many as 58. The research questionnaire used was validated using expert judgment techniques. Data from the questionnaire was processed quantitatively with the percentage technique. The results showed that the head of MAN Tolitoli had carried out academic supervision tasks. Of all the tasks, the task of motivating teachers to use information technology in learning in each subject is the task that has the highest implementation. On the other hand, the task with the lowest implementation is to guide the teacher in compiling the syllabus for each subject in accordance with the applicable curriculum. Thus, the implementation of academic supervision of madrasah principals in several areas still needs to be improved.